Efecto de la técnica quirúrgica ovariohisterectomía sobre los niveles de glicemia en gatas - Chávez Cruz, Anderson Isack (2025)
The study evaluated blood glucose variations in 20 domestic female cats undergoing ovariohysterectomy at the Small Animal Clinic of ESPAM, measuring glucose at three time points: preoperative, intraoperative, and postoperative. The average glycemia was 97.2 mg/dL before surgery, decreased to 92.1 mg/dL during the procedure, and increased notably postoperatively to 130.4 mg/dL. These variations were statistically significant (p < 0.05), confirmed by the non-parametric Friedman test, which showed the lowest glycemia during surgery and the highest after anesthetic recovery. In the immediate postoperative period, almost all animals exhibited transient hyperglycemia without clinical signs, with values above the normal range; no symptomatic hypoglycemia was observed. No correlation was found between glucose changes and age or weight, suggesting that the alterations are mainly due to surgical and anesthetic stress. Overall, ovariohysterectomy induces a biphasic glycemic response pattern: a slight intraoperative decrease followed by postoperative hyperglycemia, consistent with stress physiology. These findings highlight the need to monitor and manage glycemia during anesthesia and the postoperative period to distinguish stress-induced hyperglycemia from true pathological conditions and to maintain metabolic balance in dogs and cats.